The geopolitics of the European super league: A historiographical approach and a media analysis of the failed project in 2021 - Ginesta, Xavier; Viñas, Carles (Frontiers in Sports and Active Living, 2023)
The main objective of this article is to analyse the reasons why the 2021 European Super League project failed. The authors ask whether, in addition to the popular clamour against a semi-closed competition, it was the combination of geopolitical interests of the different actors currently involved in European elite football that prevented the project from going ahead. The main methodological framework is based on a case study, which follows an abductive reasoning approach. To do so, on the one hand, a historiographical analysis of the case has been done; on the other hand, authors have complemented this case study with an analysis of news published on the website of five mainstream newspapers (from April to June 2021) from those countries with the most significant European football leagues: The United Kingdom (The Guardian), Spain (El País), France (Le Monde), Italy (La Repubblica) and Germany (Der Spiegel). To supplement the analysis of this phenomenon, authors have also considered other relevant news published in other mainstream press or news agencies (such as The New York Times, The Yorkshire Post, The Times, Marca, Bloomberg and Reuters). Following and abductive logic, the authors conclude that, while financially the Super League debate has not been closed, in defending the current business and competition model of European football, UEFA has had the complicity of owners and shareholders of the founding clubs outside of their traditional historical roots, as well as governments that have made football an asset because of their geopolitical positioning, such as Qatar and the UK post-Brexit.